2019
DOI: 10.1111/jcmm.14238
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐sensing ion channel 1a is involved in ischaemia/reperfusion induced kidney injury by increasing renal epithelia cell apoptosis

Abstract: Acidic microenvironment is commonly observed in ischaemic tissue. In the kidney, extracellular pH dropped from 7.4 to 6.5 within 10 minutes initiation of ischaemia. Acid‐sensing ion channels (ASICs) can be activated by pH drops from 7.4 to 7.0 or lower and permeates to Ca 2+ entrance. Thus, activation of ASIC1a can mediate the intracellular Ca 2+ accumulation and play crucial roles in apoptosis of cells. However, the role of ASICs in renal ischaemic injury is uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Blockade of ASIC1a channels in the proximal tubule attenuated Ca 2+ influx in instances of renal ischemic reperfusion and led to decreased levels of human proximal tubular cell apoptosis, indicating that ASIC1a contributes to reperfusion-induced injuries in the kidney [ 66 ]. In the brain, our studies have shown that disruption of either ASIC1 or ASIC2 genes exerted neuroprotection against ischemic brain injury [ 28 , 67 ].…”
Section: Asic-associated Pathologiesmentioning
confidence: 99%
“…Blockade of ASIC1a channels in the proximal tubule attenuated Ca 2+ influx in instances of renal ischemic reperfusion and led to decreased levels of human proximal tubular cell apoptosis, indicating that ASIC1a contributes to reperfusion-induced injuries in the kidney [ 66 ]. In the brain, our studies have shown that disruption of either ASIC1 or ASIC2 genes exerted neuroprotection against ischemic brain injury [ 28 , 67 ].…”
Section: Asic-associated Pathologiesmentioning
confidence: 99%
“…The different properties of PcTx1 and Hi1a broaden the pharmacological toolkit for studying ASIC1a and ASIC1a-related pathologies. Together these two venom peptides have provided striking pharmacological evidence that ASIC1a is involved in ischemic injuries of not just the brain, but also the heart [156] and kidney [157].…”
Section: Spider Toxins Highlight the Role Of Asic1a In Stroke-inducedmentioning
confidence: 99%
“…OPCs and OLs from OGD-induced cell death in vitro, and these effects may be mediated by STAT3, a key transcription factor (Dai et al, 2020). Importantly, IL-4 promotes OL regeneration and repairs WM integrity in stroke models (Liu et al, 2016;Song et al, 2019).…”
Section: Role Of Microg Lia In Myelination In Wmi: a Doub Le-edg Edmentioning
confidence: 99%
“…For instance, TGF‐α secreted by microglia directly protects OPCs and OLs from OGD‐induced cell death in vitro , and these effects may be mediated by STAT3, a key transcription factor (Dai et al., 2020). Importantly, IL‐4 promotes OL regeneration and repairs WM integrity in stroke models (Liu et al., 2016; Song et al., 2019). Knockout of IL‐4 in experimental models leads to WM deterioration while the intranasal administration of IL‐4 nanoparticles after stroke improves WM integrity and results in superior long‐term functional recovery in wild‐type mice (Song et al., 2019).…”
Section: Role Of Microglia In Myelination In Wmi: a Double‐edged Swordmentioning
confidence: 99%
See 1 more Smart Citation